A nanoscale porous glucose-based polymer for gas adsorption and drug delivery. (30th August 2018) - Jiang, Xiaowei; Wang, Qiuliang; Liu, Yunfei; Fu, Xiaohui; Luo, Yali; Lyu, Yinong
Abstract : A glucose-based nanoporous organic polymer with the –OH group shows significant CO2 uptake capacities and good drug release behaviour. Abstract : A glucose-based nanoporous organic polymer (glu-NOP) was designed and synthesized facilely by a Scholl coupling reaction using benzylated glucose as a single monomer. The glu-NOP exhibits a high surface area (682 m 2 g −1 ), large pore volume, and high thermal stability, making it an efficient adsorbent for CO2 capture (2.84 mmol g −1 at 1.0 bar/273 K) and separation. In addition to its capabilities for gas sorption, the highly biocompatible glu-NOP was also evaluated as a drug carrier for the delivery of a hydrophobic drug, ibuprofen (IBU) and a hydrophilic drug, 5-fluorouracil (5-FU). The solution impregnation method was used for drug loading and the drug release kinetics were determined by UV spectroscopy. The results presented here reveal that, for IBU/glu-NOP and 5-FU/glu-NOP complexes, the drug loading efficiency is about 10.7 wt% and 30 wt%, respectively. More importantly, very slow delivery of IBU was achieved under physiological conditions, which is even better than that of its analogue MIL-53(Cr, Fe). This could effectively avoid frequent and invasive dosing and improve patient compliance. This study, therefore, supports the potential of glu-NOP as a simple and stable platform for both gas uptake and drug delivery.